Chondroitin Sulfate Glycosaminoglycan Scaffolds for Cell and Recombinant Protein‐Based Bone Regeneration. (21st January 2019) - Andrews, Seth; Cheng, Albert; Stevens, Hazel; Logun, Meghan T.; Webb, Robin; Jordan, Erin; Xia, Boao; Karumbaiah, Lohitash; Guldberg, Robert E.; Stice, Steven
Abstract: Bone morphogenetic protein 2 (BMP‐2)‐loaded collagen sponges remain the clinical standard for treatment of large bone defects when there is insufficient autograft, despite associated complications. Recent efforts to negate comorbidities have included biomaterials and gene therapy approaches to extend the duration of BMP‐2 release and activity. In this study, we compared the collagen sponge clinical standard to chondroitin sulfate glycosaminoglycan (CS‐GAG) scaffolds as a delivery vehicle for recombinant human BMP‐2 (rhBMP‐2) and rhBMP‐2 expression via human BMP‐2 gene inserted into mesenchymal stem cells (BMP‐2 MSC). We demonstrated extended release of rhBMP‐2 from CS‐GAG scaffolds compared to their collagen sponge counterparts, and further extended release from CS‐GAG gels seeded with BMP‐2 MSC. When used to treat a challenging critically sized femoral defect model in rats, both rhBMP‐2 and BMP‐2 MSC in CS‐GAG induced comparable bone formation to the rhBMP‐2 in collagen sponge, as measured by bone volume, strength, and stiffness. We conclude that CS‐GAG scaffolds are a promising delivery vehicle for controlling the release of rhBMP‐2 and to mediate the repair of critically sized segmental bone defects.Stem Cells Translational Medicine 2019;8:575–585 Abstract : We investigate the use of chondroitin sulfate glycosaminoglycan (CS‐GAG) hydrogel loaded with mesenchymal stem cells (MSCs), bone morphogenetic protein 2 (BMP‐2) expressing MSCs, or recombinant BMP‐2 in bone repair, compared to a clinically used bone graft substitute when applied to a critically sized defect model. CS‐GAG loaded with recombinant BMP‐2 or BMP‐2 expressing MSCs performed similarly to the current bone graft substitute open exciting possibilities for future therapies.